Pelatihan Mendeley Bagi Guru dan Calon Guru PAUD di Kota Jayapura - Andrianus Krobo; Sirjon Sirjon; Agustinus Tandilo Mamma (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
This activity is entitled "Mendeley Training for Teachers and Prospective PAUD Teachers in Jayapura City". The target number who attended the activity was 24 people. The purpose of this activity is to facilitate and train teachers and prospective PAUD teachers in Jayapura City to be able to use Mendeley as a reference manager. The methods applied in this training are presentations, questions and answers, and hands-on practice. In carrying out this activity, the skills and competencies developed are the ability to manage references in scientific writing and the ability to make citations. Based on the results of the evaluation carried out, data were obtained showing that of the 24 participants, there were 20 participants (83.33%) who were in the very good criteria, 3 participants (12.5%) were in the good criteria, and 1 participant (4 ,17%) is in the criteria of good enough. This shows that this training activity can improve the ability and competence of participants in using Mendeley as a reference manager.